Adjuvant potential of virgin coconut oil extract on antiretroviral therapy‐induced testicular toxicity: An ultrastructural study. (12th December 2017) - Ogedengbe, O. O.; Jegede, A. I.; Onanuga, I. O.; Offor, U.; Peter, A. I.; Akang, E. N.; Naidu, E. C. S.; Azu, O. O.
Summary: The effects of Virgin coconut oil as an adjuvant to highly active antiretroviral therapy (HAART) were investigated on the testicular ultrastructure and biochemical markers in rats. Twenty male Sprague‐Dawley rats, weighing 153‐169 g were divided into four groups and treated as follows: control A (distilled water), B (HAART), C (HAART+Virgin coconut oil 10 ml/kg) and D (Virgin coconut oil [VCO] 10 ml/kg). Testicular segments were evaluated using transmission electron microscopy. Serum was assayed for testosterone, luteinising hormone, follicle stimulating hormone and testicular tissue for malondialdehyde and glutathione. Ultrastructure of basement membrane (Bm), mitochondria and spermatocytes was normal in the control group. HAART‐treated group showed significant increase ( p < .01) in Bm thickness with significant decrease in Leydig cell nuclear diameter ( p < .05) and volume ( p < .01) when compared with control group. Mitochondrial cristae appear collapsed, and Sertoli cells showed cytoplasmic vacuolations. HAART+VCO group showed improved ultrastructural details in Bm, and Sertoli cell and Leydig cells show abundant lipid droplets. Virgin coconut oil‐treated group showed thinning of Bm with otherwise normal ultrastructural features of organelles. HAART‐treated group showed significant increase ( p < .01) in testosterone levels. There was no significant effect on malondialdehyde and glutathione levels. Virgin coconut oil improved testicular morphology and reversed HAART‐induced ultrastructural alterations. Further studies on putative mechanism are required.